2019
DOI: 10.1007/s40195-019-00939-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mechanical Properties of Pure Zirconium via Friction Stir Processing

Abstract: Friction stir processing (FSP), as a new kind of severe plastic deformation technique, can refine and homogenize the microstructure of metallic material. In this study, the effect of FSP on the microstructure and mechanical properties of pure Zr was investigated using electron backscatter diffraction analysis, microhardness and room-temperature tensile testing. The fine-grained (FG) structure with an average grain size of ~ 5.3 μm was obtained in the processed zone, where the average microhardness was ~ 198 HV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Figure 3 shows the transverse cross section macrostructure of FSP samples with different rotation rates. They all exhibited a basin-shaped structure widening toward the upper regions [25]. Moreover, it can be observed that the depth of the widening zone became high with increasing rotation rate (shown by the red lines), which indicated that with the increase of the rotation rate, the influence of the shoulder became strong.…”
Section: Low Magnification Overviewmentioning
confidence: 90%
“…Figure 3 shows the transverse cross section macrostructure of FSP samples with different rotation rates. They all exhibited a basin-shaped structure widening toward the upper regions [25]. Moreover, it can be observed that the depth of the widening zone became high with increasing rotation rate (shown by the red lines), which indicated that with the increase of the rotation rate, the influence of the shoulder became strong.…”
Section: Low Magnification Overviewmentioning
confidence: 90%